Lower 30-Day Mortality after Early Stent Thrombosis with Bivalirudin vs Heparin - Rizzo, Toni (MD Conference Express, 2014)
The risk of subacute (≤30 days) stent thrombosis (ST) is high after primary percutaneous intervention (PCI) for STEMI. This article presents the results of a pooled analysis of the international, open-label HORIZONS-AMI and EUROMAX trials. The aim of the analysis was to determine the independent predictors for subacute ST and evaluate mortality after ST according to the antithrombotic therapy used for primary PCI.